Effect of Vitamin D Supplementation during Pregnancy on Birth Weight: A Case-Control Study - Parisa Elmee; Seyyed Shahrokh Taghavi (Mashhad University of Medical Sciences, 2017)
ABSTRACTBackground: Previous studies revealed that maternal serum level of vitamin D can influence neonatal outcomes. In this controlled trial, we evaluated the effect of vitamin D supplementation during pregnancy on birth weight.Methods: In this interventional study, we enrolled 67 pregnant women (gestation: 10 weeks), who referred to Seyyedal Shohada Hospital during two years (from January 2014) with vitamin D less than 30 ng/ml. From gestational age of 14-24 weeks, vitamin D (50,000 IU/week) was administered to the patients, and its level was measured again in the 24th week of gestation. At this time, patients with vitamin D more than 30 ng/ml served as the intervention group, while the remaining patients were excluded (n=55 patients). In the control group, the level of vitamin D was measured at the time of delivery.Results: The mean vitamin D level in the intervention group was 43.04±20.09 ng/ml. The baseline patient characteristics such as gravidity, parity, and the number of deliveries were not significantly different between the two groups. However, the two groups were significantly different regarding neonates' characteristics such as birth weight, height, and headcircumference.Conclusion: Our findings showed that administrating vitamin D during pregnancy increases the mean values of neonatal weight, head circumference, and height.